(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: Our main aim of the research is to Optimization of feed and spindle speed levels for surface roughness and cylindricity tolerance of the drilled holes in liquid stir casted Al6061 hybrid metal matrix composite reinforced with 15% weight fraction of B4C+Fly ash and comparing with that of as-cast Al6061. Materials and Methods: In this study, Al6061 aluminum casting plate with a thickness of 10 mm was used. Al6061 aluminum was normalized at 750 degrees Celsius using a muffle furnace.and optimized with different spindle speed and feed rate. And taking the surface roughness and cylindricity tolerance. .Test samples (N = 20) were taken from each plate of experimental group ( B4C,Fly ash) and control group (Al6061) GPower:82%. Results: To measure the surface roughness and cylindricity tolerance of the drilled holes at different spindle speed and various feed rate and to optimize with the output values.with insignificance value of 0.4485 (p>0.05). Conclusion: The surface roughness and cylindricity tolerance tolerance will be compared between the control and experimental groups based on spindle speed and feed rate, as well as knowing the material properties.